2011
DOI: 10.1063/1.3647415
|View full text |Cite
|
Sign up to set email alerts
|

Backward-meson photoproduction at SPring-8∕LEPS

Abstract: Photoproductions of S 0 and K mesons from protons were measured at backward angles. Bump structures were observed in both reaction, and a strong angular distribution of photon asymmetries was found in S 0 production. These structures are discussed connecting with baryon resonances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 4 publications
3
43
2
Order By: Relevance
“…It was found that in both cases the inclusion of this factor results in an increase of χ 2 and, as a consequence, it was concluded that the consistency problem did not originate from an error in the photon flux normalization. However, subsequent measurements of the K + Λ photoproduction cross section [25][26][27] are found to be more consistent with the result of CLAS 2006 collaboration [22]. After that, most analyses of the K + Λ photoproduction use the SAPHIR data only up to W = 1.7 GeV [1,2,19,28,29].…”
Section: Introductionmentioning
confidence: 65%
“…It was found that in both cases the inclusion of this factor results in an increase of χ 2 and, as a consequence, it was concluded that the consistency problem did not originate from an error in the photon flux normalization. However, subsequent measurements of the K + Λ photoproduction cross section [25][26][27] are found to be more consistent with the result of CLAS 2006 collaboration [22]. After that, most analyses of the K + Λ photoproduction use the SAPHIR data only up to W = 1.7 GeV [1,2,19,28,29].…”
Section: Introductionmentioning
confidence: 65%
“…[4,12]), or perhaps it is the signature of a KKN dynamically-generated resonance [13,6]. There is good agreement between CLAS and LEPS [14] at forward angles. New measurements at CLAS have been performed using the so-called "g11" data set, obtained for pentaquark searches, but which has provided copious data for other reaction channels.…”
Section: Measured Observablesmentioning
confidence: 79%
“…The plot in Figure 12 indicates that very few kaon photoproduction data were available before the start of the century. Initial measurements by SAPHIR [132,133], SPring-8 [134,135,136] and GRAAL [137,138] have been added to by a comprehensive campaign of measurements by CLAS [139,140,141,142,143]. It should be noted that, at the time of writing, a recently published paper by the BES Collaboration [144], and a study of kaon photoproduction at CLAS [145] have cast doubt on the previously quoted value of the weak decay parameter α − of the Λ.…”
Section: Kaon Photoproductionmentioning
confidence: 99%